Recycling of Date Pits Into a Green Adsorbent for Removal of Heavy Metals: A Fractional Factorial Design-Based Approach - Al-Saad, Khalid; El-Azazy, Marwa; Issa, Ahmed A.; Al-Yafie, Asma; El-Shafie, Ahmed S.; Al-Sulaiti, Maetha; Shomar, Basem (Frontiers in Chemistry, 2019)
Abstract Date pits (DPs) have been recycled into a low-cost adsorbent for removing of selected heavy metals (HMs) from artificially contaminated aqueous solutions. Adsorption of targeted HMs, both by raw date pits (RDP) and burnt date pits (BDP) was tested. Results showed that BDP is more efficient as an adsorbent and mostly adsorbing Cu(II). A novel approach; fractional factorial design (2k-p – FrFD) was used to build the experimental pattern of this study. The effects of four factors on the maximum percentage (%) of removal (Y) were considered; pH, adsorbent dose (AD), heavy metal concentration (HMC), and contact time (CT). Statistically significant variables were detected using Pareto chart of standardized effects, normal and half-normal plots together with analysis of variance (ANOVA) at 95.0 confidence intervals (CI). Optimizing (maximizing) the percentage (%) removal of Cu(II) by BDP, was performed using optimization plots. Results showed that the factors: pH and adsorbent dose (AD) affect the response positively. Scanning electron microscopy (SEM) was used to study the surface morphology of both adsorbents while fourier-transform infrared spectroscopy (FTIR) was employed to get an idea on the functional groups on the surface and hence the adsorption mechanism. Raman spectroscopy was used to characterize the prepared adsorbents before and after adsorption of Cu(II). Equilibrium studies show that the adsorption behavior differs according to the equilibrium concentration. In general, it follows Langmuir isotherm up to 155 ppm, then Freundlich isotherm. Free energy of adsorption (∆Gad) is -28.07 kJ/mole, when equilibrium concentration is below 155 ppm, so the adsorption process is spontaneous, while (∆Gad) equals +17.89 kJ/mole above 155 ppm, implying that the process is non-spontaneous. Furthermore, the adsorption process is a mixture of physisorption and chemisorption processes, which could be endothermic or exothermic reactions. The adsorption kinetics were described using a second order model.